Solve for y 5(90-7y)=y-126

Math
5(90-7y)=y-126
Simplify 5(90-7y).
Tap for more steps…
Apply the distributive property.
5⋅90+5(-7y)=y-126
Multiply.
Tap for more steps…
Multiply 5 by 90.
450+5(-7y)=y-126
Multiply -7 by 5.
450-35y=y-126
450-35y=y-126
450-35y=y-126
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract y from both sides of the equation.
450-35y-y=-126
Subtract y from -35y.
450-36y=-126
450-36y=-126
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 450 from both sides of the equation.
-36y=-126-450
Subtract 450 from -126.
-36y=-576
-36y=-576
Divide each term by -36 and simplify.
Tap for more steps…
Divide each term in -36y=-576 by -36.
-36y-36=-576-36
Cancel the common factor of -36.
Tap for more steps…
Cancel the common factor.
-36y-36=-576-36
Divide y by 1.
y=-576-36
y=-576-36
Divide -576 by -36.
y=16
y=16
Solve for y 5(90-7y)=y-126

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top